Role of extracellular matrix components and structure in new renal models in vitro - Lacueva-Aparicio, Alodia; Lindoso, Rafael Soares; Mihăilă, Silvia M.; Giménez, Ignacio (Frontiers in Physiology, 2022)
The extracellular matrix (ECM), a complex set of fibrillar proteins and proteoglycans, supports the renal parenchyma and provides biomechanical and biochemical cues critical for spatial-temporal patterning of cell development and acquisition of specialized functions. As in vitro models progress towards biomimicry, more attention is paid to reproducing ECM-mediated stimuli. ECM’s role in in vitro models of renal function and disease used to investigate kidney injury and regeneration is discussed. Availability, affordability, and lot-to-lot consistency are the main factors determining the selection of materials to recreate ECM in vitro. While simpler components can be synthesized in vitro, others must be isolated from animal or human tissues, either as single isolated components or as complex mixtures, such as Matrigel or decellularized formulations. Synthetic polymeric materials with dynamic and instructive capacities are also being explored for cell mechanical support to overcome the issues with natural products. ECM components can be used as simple 2D coatings or complex 3D scaffolds combining natural and synthetic materials. The goal is to recreate the biochemical signals provided by glycosaminoglycans and other signaling molecules, together with the stiffness, elasticity, segmentation, and dimensionality of the original kidney tissue, to support the specialized functions of glomerular, tubular, and vascular compartments. ECM mimicking also plays a central role in recent developments aiming to reproduce renal tissue in vitro or even in therapeutical strategies to regenerate renal function. Bioprinting of renal tubules, recellularization of kidney ECM scaffolds, and development of kidney organoids are examples. Future solutions will probably combine these technologies.